Studi Etika Tentang Ajaran-Ajaran Moral Masyarakat Banjar - Sumasno Hadi, Sumasno Hadi (TASHWIR, 2015)
Based on the philosophy and the cosmology of Banjar people, the ethics theory that can raised is a religio-teleological ethics. This concept of ethics has stated that the value of happiness (eudeaimonia) as the goal of life was the quality of a happy life and hereafter. So, the ethical telos or goal is the happiness in a religious orientation. The happiness of the world is less weighty than the happiness of the life hereafter. It can be confirmed that the eudemonistic ethics of Banjar people is the concept of religious ethics. In addition to the religio-teleological and religio-eudoministic,, the Banjar ethics have also declared themselves as the harmony ethics, as well as the ethics of virtue and obligation.Keywords: The ethics of Banjar, the ethics of religio-teleologis, moral philosophy, moral teachingsBerdasarkan pandangan hidup (falsafah) dan kosmologi masyarakat Banjar, konsep/teori etika yang dapat diajukan adalah etika religio-teleologis. Konsep etika ini menyatakan bahwa nilai kebahagiaan (eudeaimonia) sebagai tujuan hidup adalah kualitas bahagia dunia-akhirat. Jadi telos atau tujuan etisnya adalah kebahagian secara religius (orientasi agama). Kebahagiaan dunia kurang berbobot dibandingkan dengan kebahagiaan akhirat. Dari sini dapat dinyatakan pula, etika eudemonistik masyarakat Banjar adalah konsep etika yang religius. Selain etika religio-teleologis dan religio-eudemonistik, etika Banjar juga menyatakan diri sebagai etika harmoni, juga etika keutamaan dan etika kewajiban.Kata kunci: etika Banjar, etika religio-teleologis, ajaran moral, filsafat moral